x^2 -12x=36
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 4:
\(x^3-2x^2+x=x\left(x-1\right)^2\)
\(5\left(x-y\right)-y\left(x-y\right)=\left(x-y\right)\left(5-y\right)\)
\(x^2-12x+36=\left(x-6\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x^2-12x+36=x^2-2.x.6+6^2=\left(x-6\right)^2\)
b) \(12x-x^2-36=-\left(x^2-12x+36\right)=-\left(x-6\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(x^2+12x+36=0\)
=>\(x^2+2\cdot x\cdot6+6^2=0\)
=>\(\left(x+6\right)^2=0\)
=>x+6=0
=>x=-6
b: \(4x^2-4x+1=0\)
=>\(\left(2x\right)^2-2\cdot2x\cdot1+1^2=0\)
=>\(\left(2x-1\right)^2=0\)
=>2x-1=0
=>2x=1
=>x=1/2
c: \(x^3+6x^2+12x+8=0\)
=>\(x^3+3\cdot x^2\cdot2+3\cdot x\cdot2^2+2^3=0\)
=>\(\left(x+2\right)^3=0\)
=>x+2=0
=>x=-2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\sqrt{x^2-12x+36}-x=3\)
\(\Leftrightarrow x^2-12x+36=x^2+6x+9\)
\(\Leftrightarrow-18x=27\)
hay \(x=-\dfrac{3}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^4-2x^3-12x^2+12x+36=x^4+x^2+36-2x^3+12x-12x^2-x^2\)
\(=\left(x^2-x-6\right)^2-x^2=\left(x^2-6\right)\left(x^2-2x-6\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
=> \(x^2-12x+36=0\Leftrightarrow\left(x-6\right)^2=0\Rightarrow x=6\)
12x - x2 - 36=0
=>- x2 + 12x - 36 = 0
Giải phương trình trên máy tính ta có :
X= 6
Vậy x = 6
Study well
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(4\left(6-x\right)+x^2-12x+36=0\)
\(24-4x+x^2-12x+36=0\)
\(x^2-16x+60=0\)
\(x^2-2x8+8^2-8^2+60=0\)
\(\left(x-8\right)^2-4=0\)
\(\left(x-8\right)^2=4\)
\(\left(x-8\right)^2=\left(\pm2\right)^2\)
\(\orbr{\begin{cases}x-8=2\Rightarrow x=10\\x-8=-2\Rightarrow x=6\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,\Leftrightarrow4x^2+4x+1-4x^2-12x=9\\ \Leftrightarrow-8x=8\Leftrightarrow x=-1\\ b,\Leftrightarrow\left(x-6\right)^2=0\Leftrightarrow x=6\)
\(x^2-12x=36\)
\(\Leftrightarrow\left(x-6\right)^2=72\)
\(\Leftrightarrow\orbr{\begin{cases}x=\sqrt{72}+6\\x=6-\sqrt{72}\end{cases}}\)